Altered erythrocyte morphology in Mexican adults with prediabetes and type 2 diabetes mellitus evaluated by scanning electron microscope. (12th March 2019) - Loyola-Leyva, Alejandra; Loyola-Rodríguez, Juan Pablo; Terán Figueroa, Yolanda; González, Francisco Javier; Atzori, Marco; Barquera Cervera, Simón
Abstract : People living with prediabetes and type 2 diabetes mellitus presented a significant decrease in the diameter and height of erythrocytes compared with healthy individuals, . HbA1c, glucose, triglycerides, cholesterol, LDL cholesterol, systolic blood pressure, BMI, waist and hip circumference were significantly associated with diameter and height alterations. Abstract: Aim: To evaluate the erythrocyte morphology in people with prediabetes, T2DM and healthy subjects in a Mexican population and its association with biochemical parameters. Methods: Cross-sectional study consisted of three groups: healthy (HG), people with prediabetes (PG) and with T2DM (DMG). A blood sample was obtained from all participants to assess the erythrocyte morphology, and levels of HbA1c, glucose and lipid profile. Anthropometrical parameters were also evaluated. Results: It was observed that compared with healthy individuals, people with prediabetes presented a significant decrease in the diameter (−0.08 μm, P = 0.014) and height (−0.07 μm, P = 0.004), as well as people with T2DM (−0.33 μm, P < 0.001 in diameter; and −0.36 μm, P < 0.001 in height). Besides, it was found a significant difference in diameter (−0.25 μm, P < 0.001) and height (−0.29 μm, P < 0.001) between the PG and DMG. No significant differences in the axial ratio between groups. Also, HbA1c, glucose, triglycerides, cholesterol, LDL cholesterol, systolic blood pressure, weight, BMI, waist and hip circumference were significantly associated with diameter and height. Conclusions: Erythrocyte morphological alterations can serve as an indicator of early diagnosis of T2DM and a factor implicated in the course of the clinical condition, so the correction of these alterations could serve as a treatment for prediabetes and T2DM. It is essential to promote constantly checkups of biochemical and anthropometrical parameters, as well as erythrocyte morphological alterations to prevent the onset of prediabetes and T2DM and possible clinical complications.